2021
DOI: 10.1101/2021.07.21.451321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlike Chloroquine, mefloquine inhibits SARS-CoV-2 infection in physiologically relevant cells and does not induce viral variants

Abstract: Repositioning of clinical approved drugs could represent the fastest way to identify therapeutic options during public health emergencies, the majority of drugs explored for repurposing as antivirals for 2019 coronavirus disease (COVID-19) have failed to demonstrate clinical benefit. Without specific antivirals, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic continues to cause major global mortality. Antimalarial drugs, such as chloroquine (CQ)/hydroxychloroquine (HCQ) and mefloquine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Nine of the approved drugs are formulated for oral use; interferon alpha and ciclesonide are inhaled therapeutics. Two other agents appeared to synergize with RDV in Calu3 cells but were tested only at two doses: the approved oral drug mefloquine ( 98 ) and the investigational drug brilacidin ( 88 ). Of the pairs in Table 1 , only the combination of MPV plus brequinar has been tested in an animal model, where it reduced viral loads and lung pathology favorably compared to either drug alone ( 77 ).…”
Section: Current Progress On Drug Combinations Against Sars-cov-2mentioning
confidence: 99%
“…Nine of the approved drugs are formulated for oral use; interferon alpha and ciclesonide are inhaled therapeutics. Two other agents appeared to synergize with RDV in Calu3 cells but were tested only at two doses: the approved oral drug mefloquine ( 98 ) and the investigational drug brilacidin ( 88 ). Of the pairs in Table 1 , only the combination of MPV plus brequinar has been tested in an animal model, where it reduced viral loads and lung pathology favorably compared to either drug alone ( 77 ).…”
Section: Current Progress On Drug Combinations Against Sars-cov-2mentioning
confidence: 99%
“…Combination therapy, which involves two or more therapeutic agents, has been a cornerstone of antiviral therapy. For example, combination treatment involving at least three different antiretroviral drugs (two nucleoside reverse transcriptase inhibitors, and one either an integrase strand transfer inhibitor (INSTI)-a non-nucleoside reverse transcriptase inhibitor-or a protease inhibitor) is recommended for the standard treatment of HIV [169]. Such a combination therapy could inhibit HIV replication, allowing the immune system to overcome the infection and prevent AIDS.…”
Section: Combinational Therapy Of Natural Compoundsmentioning
confidence: 99%
“…Subsequent studies using polymerase extension assays demonstrated that those compounds can be incorporated by SARS-CoV-2 RdRp (11,12), disrupting the RNA synthesis by direct chain termination (11) or accumulation of deleterious mutations in viral genome (12). However, in the cell-based assays, inhibition of SARS-CoV-2 replication by those compounds were low or nondetectable (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of NUCs with HCV NS5A inhibitors, which were predicted to target SARS-CoV-2 nsp14 exonuclease domain, increased the antiviral potency of NUCs against SARS-CoV-2 (13,14).…”
Section: Introductionmentioning
confidence: 99%